The transcription factor combination MEF2 and KLF7 promotes axonal sprouting in the injured spinal cord with functional improvement and regeneration-associated gene expression - Callan L. Attwell; Inés Maldonado-Lasunción; Ruben Eggers; Bastiaan A. Bijleveld; Ward M. Ellenbroek; Natascha Siersema; Lotte Razenberg; Dédé Lamme; Nitish D. Fagoe; Ronald E. van Kesteren; August B. Smit; Joost Verhaagen; et al. (Molecular Neurodegeneration)
Abstract Background Axon regeneration after injury to the central nervous system (CNS) is limited by an inhibitory environment but also because injured neurons fail to initiate expression of regeneration associated genes (RAGs). The potential of strong RAG expression to promote regeneration in the CNS is exemplified by the conditioning lesion model, whereby peripheral nerve injury promotes regeneration of centrally projecting branches of the injured neurons. RAG expression could potentially be induced by delivery of the right set of transcription factors (TFs). We here aim to identify TF combinations that activate this program. Methods We first analysed binding site motifs in promoters of the RAG program to identify nine candidate growth-promoting TFs. These were systematically screened in vitro to identify combinations that had potent neurite-growth promoting activity. Next, adeno-associated viral vectors were used to express these TF combinations in vivo in L4/L5 dorsal root ganglia to test whether they would promote regeneration in a spinal cord injury model (dorsal column lesion) in female rats. To determine whether they could activate the RAG program we carried out gene expression profiling on laser-dissected dorsal root ganglion neurons specifically expressing these TF combinations, and of DRG neurons that had been axotomized. Results Promoter analysis identified ATF3, Jun, CEBPD, KLF7, MEF2, SMAD1, SOX11, STAT3 and SRF as candidate RAG-activating TFs. In vitro screening identified two TF combinations, KLF7/MEF2 and ATF3/KLF7/MEF2, that had potent neurite-growth promoting activity, the latter being the more powerful. In vivo, KLF7/MEF2, but not ATF3/KLF7/MEF2 or KLF7 or MEF2 alone, promoted axonal sprouting into the dorsal column lesion site and led to improved functional recovery. Gene expression profiling revealed that unexpectedly, the MEF2-VP16 construct used had little transcriptional activity in vivo, suggesting additional steps may be required to achieve full MEF2 activity. All combinations except MEF2 alone induced RAG expression mirroring that induced by axotomy to significant extents, while ATF3/KLF7/MEF2, KLF7 and ATF3, but not KLF7/MEF2 also induced apoptosis-related genes which may hinder regeneration. Conclusions The TF combination KLF7/MEF2 partially mimics the conditioning lesion effect, inducing axonal sprouting into a dorsal column lesion and driving significant RAG expression, and also promotes functional improvement.